PENGARUH PENERAPAN PROGRAM APLIKASI SISTEM RITEL DALAM MENINGKATKAN KOMPETENSI MAHASISWA PENDIDIKAN TATA NIAGA - Nugroho, Jonet Ariyanto (MIIPS, 2008)
This study investigates the influence application of Retail System to increase the competency student of Tata Niaga education. Implementing application of Retail System Aplication already applying in Tania Mini Market. The application of retail system in Tania maked by student, almost same with activity in generally mini market. So, this practice activity to give the student competency to arrange and operation the mini market. Finally the student can to competent in work market or to enter retail business. Explanation of this problem is very important in teory or practice that is can to increase and to expand knowledge the student to operations mini market. In practice, application of retail system can to increase process study in laboratorium Tata Niaga education so aims of education can be reached.Â